Teachers’ Strategies for Managing Adolescent Students with Maladaptive Behaviours in Ghana - Amoah, Charles Agyei; Dontoh, Samuel; Adjei, Augustine; Amanfo, Barnabas Addai (International Journal of Scientific Research and Management (IJSRM), 2020)
Maladaptive behavior is arguably the most common disruptive behaviour among adolescents and in order to transform these students into productive members in the society, the need for quality education cannot be overrated. It is in this regard that this study seeks to examine the strategies that teacher use to manage maladaptive behaviours in Offinso Municipality. A quantitative approach and an explanatory research design was adopted to ensure that the right data is collected and the appropriate analytical techniques are used. Further, Krejcie and Morgan (1970) and stratified random sampling was used to select a total of 171 teachers from the three schools with the aid of questionnaire as the research instrument. All ethical issues were strictly adhered to ensure Full Corporation with the study. SPSS version 22 was used to code and capture the data collected. A combination of descriptive analysis and sequential linear regression was used to analyse the data. The results showed that the students of the three schools in the Offinso Municipality exhibit maladaptive behaviour and the teachers have adapted strategies that significantly manages the maladaptive behaviours. The factors influencing maladaptive behaviour in the adolescents includes parental, environmental and the school. For resource allocation and policy implications, management should first consider committing resources to enhancing the teacher’s strategy before considering the three category of factors influencing the maladaptive behaviour in the adolescent students. Further, management should engage the parents, the community leaders and government to develop strategies in mitigating maladaptive behaviour in adolescent students. The need for counselling service centres cannot be overrated besides orientation practices.